Permeability of soils at elevated permeant pressures - Bennett, J. P., author; U.S. Department of the Interior, Bureau of Reclamation, publisher (Colorado State University. Libraries, 1966)
Laboratory studies were made to develop and evaluate test apparatus and procedures for pressurized soil permeability tests. Pressures were applied to headwater and tail water to reduce the volume of free air in the soil and dissolve the air in the permeant water. Primary objective was to determine feasibility of using the high-pressure permeability test as a standard, since the test can be performed in as little as 1/10 the time of the standard test now in use. Analytical equations were developed for predicting the increment of pressure required to saturate a given soil as a function of initial degree of saturation, pore air pressure, and coefficient of air solubility in water. Some conclusions were: (1) Dry density increases during the test with accompanying decrease in permeability. (2) Specimen compaction method considerably influences permeability values obtained. (3) In general, saturation is not achieved using the saturation pressure increment as computed by equations based on assumed final conditions. (4) Main advantage of the test procedure is the speed with which maximum permeability values can be obtained.
CER66JPB7.
July 7, 1966.
Support provided by the National Science Foundation.
Keywords: Soil permeability; Soil mechanics